CORRELATION BETWEEN ADDED ROSSELA (HIBISCUS SABDARIFFA L) TO PHYSICAL AND CHEMICAL PROPERTIES OF KALAMANSI FRUIT ORANGE POWDER AS A DRINK - Kurnia Herlina Dewi; Zulman Efendi; Ida Apri Yanti (Jurnal Agroindustri, 2017)
The product development effort based on kalamansi aims to extend the shelf life, make the product more durable and increase the added value and fulfill the consumer demand for the practicality in the use. The purpose of this study was Determine the effect of rossela addition to physical and chemical characteristics, determine the effect of rossela addition to organoleptic characteristics. The research design used in this study was Completely Randomized Design (RAL) with treatment of percentage of dry rosella powder: 0%, 2.5%, and 5%, in which each treatment was repeated three repetitions so that nine treatment units were obtained. Parameters observed in water content, solubility rate, pH and organoleptic (flavor, aroma, color). The results showed that the greater percentage of rosella addition, water content, solubility rate and vitamin C were higher, following the equation y = 0,188x + 3,7733 for water content, Y = 6,4x + 37,767 for soluble time . Each addition of rosella occurs a decrease in pH following the equation Y = -0.086x + 4.215. While vitamin C levels follow the equation Y = 5,514x + 16,818. The panelist's preference for the product is good; evidenced by the three tests (aroma, flavor and color) have the highest level of addition of 5% rosella addition. The higher the rosella addition rate ratio the panelist prefers. The panelist's favorite level is at an average of 3 which is quite like.